Mobile clinic approach towards hard-to-reach populations' health in Roman suburban settings. (13th November 2019) - Corsaro, A; Marotta, R; Angelone, D F; Biagiarelli, F S; Terenzi, F; Zampa, A; Buonuomo, E; Galizi, M C; Giuffrida, F; Giampaolo, R
Abstract: : Among other vulnerable populations, Sinti and Roma ethnicity people are the ones more likely living in precarious housing conditions such as settlements, especially in Roman suburban and deprived neighbourhood. These hard-to-reach communities usually present poor health outcomes and reduced life expectancy. Since 2016, the project Nontiscordardimé (a partnership of Bambino Gesù Children's Hospital, OSA Health Workers Cooperative and Vicariatus Urbis) provided 3 outreach per week in two different peripheral settings ensuring to children specialized visits, nutritional screening, growth monitoring and vaccinations by means of a mobile clinic. When necessary, second level examinations have been arranged in the hospital. Personal data, detected pathologies and services provided have been collected from January 2016 to December 2018. Main diseases detected during 2.226 examinations in Gipsy settlements were respiratory infection (26, 3%), skin infection and parasitosis (13.3.%). Moreover 7, 5% of visited children had malnutrition and 3, 4 % presented oral hygiene related issues. Only 40% of planned second level examination and only 51% of planned hospital admission have been carried out. During outreach in parishes of suburban areas, 1.411 examinations have been performed, encountering mostly respiratory disease (30%), asthmatic bronchitis (8%), dermatitis (5, 8%) and allergic rhinitis (3, 8%). Adherence to hospital examination and admission reach respectively 72% and 85%. Poor housing, isolation and overcrowding are significant barriers to prevention and health care even if the national health system provides universal coverage, and free care. Indeed disease prevalence in gipsy settlements was mainly related to socio-economical and housing condition (poor hygiene, overcrowding) whereas others peripheral urban setting, even when deprived, showed an epidemiological framework close to the general population where asthmatic and allergic disorders are prevalent. Key messages: Mobile clinics can close the gap between health services and disadvantaged children and hard-to-reach populations. Outreach can be a mean of promotion, prevention and health services inclusion.